3D printed magnetic digital microfluidics for biomedical applications - Kanitthamniyom, Pojchanun (Nanyang Technological University, 2021)
Point-of-care testing (POCT) is one of the best alternative solutions to centralized testing. It utilizes a small platform that is easy to operate and can be performed near the patient’s location without the need of a central laboratory. Although some POCT devices have already been commercialized and widely used, many POCT technologies still have limitations and face difficulties in entering the market. Microfluidics is one of the most important components of a POC platform. However, conventional microfluidics has some drawbacks. For example, its external fluidic couplings and fluid pumps are often bulky and hinder its applications in POCT. In contrast, digital microfluidics can manipulate discrete droplets without the need for external fluidic coupling. Magnetic digital microfluidic (MDM) is a platform that is capable of both manual and automated droplet control by using magnetic force to manipulate magnetic particles in the droplets on a modified open surface. Surface energy traps, which are high surface energy regions on the modified surface in the form of both physical structures and chemical surface modification, are introduced for a variety of droplet operations. Yet, current fabrication and modification procedures are tedious and time-consuming. Furthermore, existing MDM platforms uses monolithic fabrication techniques, which are desirable for accurate alignment of complex architectures for the fabrication. But any small changes in device design may call for an entirely new redesign for the monolithic fabrication process. Therefore, this thesis focuses on developing new fabrication and surface modification approaches to improve the performance of magnetic digital microfluidics using both 3D printing and bioinspired surface modification methods to simplify the fabrication of surface energy trap-enabled magnetic digital microfluidic platform and applying the proposed platforms to POC applications. Thus, the first part of this thesis focuses on understanding the phenomena of droplet operation on the magnetic digital microfluidic platform. The second part of the thesis reports a novel rapid surface modification method of creating surface energy traps for magnetic digital microfluidics. The protocol of fabrication polydopamine surface energy trap on the Teflon-coated glass substrate was characterized and optimized . The droplet operations, including particle extraction, liquid dispensing, liquid patterning, and cross-platform transfer, were demonstrated with the polydopamine surface energy traps in both single-plate and two-plate configurations. Here, the detection of hepatitis B surface antigen using enzyme-linked immunosorbent assay (ELISA) was demonstrated on the new platform for the potential diagnostics of hepatitis. The third part of this thesis shares a 3D printing method used for fabricating the physical structure-assisted magnetic digital microfluidic platform. The 3D printing models for modular magnetic digital microfluidic were characterized and optimized for suitable POCT applications. Together with PDA modification, a 3D-printed modular magnetic digital microfluidic architecture was created for on-demand bioanalysis such as biomarker sensing, pathogen identification, antibiotic resistance determination, and biochemical quantification. The last part of this thesis shows the combination of 3D-printed physical structures and polydopamine-enabled rapid surface modification. It also shows a novel development of magnetic digital microfluidic platform called ‘Cbac-MDM’ for the diagnostics of carbapenemase-producing Enterobacteriaceae. Cbac-MDM is more user-friendly and well-suited for point-of-care applications. I believe that our innovations provide a new avenue for microfluidic point-of-care assay development. With its high portability and configurability, the novel magnetic digital microfluidic platform would expand the applicability of point-of-care testing in the near future.